IDENTIFICATION AND RANKING OF EFFECTIVE INDICATORS IN EMPLOYEE EMPOWERMENT TO IMPLEMENT KNOWLEDGE MANAGEMENT WITH AHP APPROACH (CASE STUDY: KALEH CO.) - Nader Shaikholeslmi Kendlusi; Atefeh Ziari (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The purpose of this study is to identify and rank the effective indicators in employee empowerment to implement knowledge management with AHP approach (Case study: Kaleh Company). This research is applied in terms of purpose and descriptive-survey method. The statistical population of the present study includes familiar experts in the field of employee empowerment and knowledge management and managers of Kaleh Company. 8 experts have been selected to perform the Delphi method and 7 experts have been selected to perform the AHP method. Hypotheses and test questions were analyzed based on the data obtained from the relevant questionnaires using Excel and EXPERT-CHOICE software. In this study, the tests were performed through a checklist and localization of the questionnaire and measuring the opinion of experts to identify the components and then based on it and the combination of known factors with the opinions of experts to measure the factors and determine their weight using AHP test and prioritization. Factors are discussed. The results show that among the identified criteria, the capacity building criterion with a final score of 0.166 in the first rank and the criterion of individual factors with a final score of 0.052 in the tenth and last rank and also the rest of the criteria in order of priority (cultural factors criterion with The final score in the second rank, the criterion of organizational creativity with the final score in the third rank, the criterion of organizational motivation with the final score in the fourth rank, the criterion of organizational learning with the final score in the fifth rank, the criterion of education with the final score in the sixth rank, the criterion of environmental factors with the score The final is in the seventh place, the criterion of interpersonal factors with the final score is in the eighth place and the criterion of information technology with the final score is in the ninth place).